Kearifan Lokal Sebagai Budaya Hukum Masyarakat yang Harmonis dan Beragama - Ambarwati, Dewi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This article focuses on the role of local wisdom as a legal culture of a harmonious and religious society, with an epistemological study in Pancasila Village, Kesamben Village, Ngajum District, Malang Regency. This research shows that local wisdom can be an important foundation in building a harmonious and religious society. Through qualitative analysis, this study found that local traditions and values in Pancasila Village have succeeded in building harmony and tolerance between religious communities. This local wisdom includes not only value and belief systems, but also social rules and work ethics that support harmonious social dynamics. The results of this study show that the integration of local wisdom with Islamic values can increase harmony and tolerance in society, thus encouraging the development of a more harmonious and religious society. Therefore, local wisdom can be used as an effective strategy in maintaining the resilience of Pancasila ideology and grounding Pancasila values in the community.